HUMAN–AI COLLABORATION AND ELECTRONIC AUDIT QUALITY: THE ROLE OF SUSTAINABLE AUDIT DIGITAL INNOVATION - Sudi Dodo Plansakti; Atta Putra Harjanto (Universitas Riau, 2026)
The rapid adoption of artificial intelligence (AI) and digital audit systems has produced inconsistent findings regarding their impact on audit quality. This study examines the determinants of electronic audit quality (E-AQ) by integrating Resource-Based View (RBV) and Unified Theory of Acceptance and Use of Technology (UTAUT), with Sustainable Audit Digital Innovation (SADI) as a moderating variable. A quantitative approach was applied to 243 auditors from 25 non-Big Four public accounting firms in Semarang using convenience sampling and PLS-SEM. General qualification, electronic qualification, independence, due professional care, assisted AI, augmented AI, autonomous AI, and SADI positively influence E-AQ, while task complexity negatively affects it. SADI moderation is selectively synergistic, significant only for augmented AI among the three AI types. Theoretically, this study extends RBV and UTAUT by establishing that organizational digital capability amplifies AI quality contributions in a type-specific rather than uniform manner, offering evidence-based guidance for sustainable audit technology adoption.